THE VIRTUOUS VOICES IN MODERN MYTHICAL NARRATIVES: A STUDY OF KAVITA KANE’S KARNA’S WIFE – THE OUTCAST’S QUEEN” - Tomar, Ms. Nirja; Dhand, Deepika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Myths, with their intricate threads weaving through the tapestry of our past, present, and future, serve as the archaic stories that intricately connect our existence. Deeply ingrained in our collective consciousness, these narratives exert a significant sway on our thoughts, influencing our actions, beliefs, and the very core of our culture, traditions, and spiritual practices. Nonetheless, nestled within the expansive fabric of the great Mahabharata epic, the longstanding voices and accounts of women have often been obscured, relegated to the periphery, their vivid tales and poignant struggles overshadowed and neglected. This evident oversight sparks the essence of the current research undertaking, aiming to delve into the themes of oppression and justice as they unravel through the eyes of the primary female protagonist and other women illustrated in the literary masterpiece "Karna’s Wife – The Outcast’s Queen" by conducting an extensive analysis. Through a meticulous exploration, the central focus revolves around resurrecting the marginalized narratives of characters like Uruvi, a figment of Kane’s imagination, embodying the resilience and indomitable spirit of women daring to challenge societal norms and structures. It becomes increasingly apparent that the oppression encountered by these characters was met with a spirited and multifaceted resistance from the female personas interwoven within the narrative, each grappling with the constraints of their outcast identity in unique and profound ways. The overarching objective of this comprehensive study lies in shedding light on the societal frameworks and historical backdrops wherein Uruvi and other female characters carve their paths, spotlighting their quests for acknowledgment, empowerment, and inclusion in a world fraught with bias and prejudice.